Analisis Pengaruh Pelatihan Dan Kompensasi Terhadap Prestasi Kerja Karyawan Pada PT. Perkebunan Nusantara X Pesantren Baru Kediri - Meviya, Nerissa Artha; Laely, Nur; Sudjiono3, Sudjiono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study's objective is to find out how employees perform at PT. Nusantara X Kediri New Islamic Boarding School plantation which is affected by training and salary. Because the research data for this study is numerical, can be checked statistically, and meets scientific criteria, namely, definite, objective, measurable, logical, and systematic. Using quantitative research methodologies. The 69 employees of PT. Nusantara X Kediri New Islamic Boarding School is a research population. The sample in the study consisting of all employees of PT. Perkebunan Nusantara X Pesantren Baru Kediri. Data collection techniques include interviews, questionnaires and documentation studies. Multiple linear regression tests, tests of classical assumptions, tests of validity and reliability, partial significance tests (t statistical test), concurrent /simultaneous significance tests (f statistical tests), and determination coefficients during the process of data analysis. The study's conclusions lead to the following conclusions: (1) Training significantly and profitably affects employee work performance, according to the findings of the regression test conducted on the second hypothesis. The results of the regression analysis related to the third hypothesis show that remuneration has a beneficial and significant impact on employee performance. (3) We can draw a conclusion from it. from the output of the first hypothesis that employee performance is affected by compensation and training at the same time. This implies that a person will perform better in the workplace if they receive greater training and salary.